2016
DOI: 10.1103/physrevd.93.104044
|View full text |Cite
|
Sign up to set email alerts
|

Stability and instability of Ellis and phantom wormholes: Are there ghosts?

Abstract: It is concluded in the literature that Ellis wormhole is unstable under small perturbations and would decay either to the Schwarzschild black hole or expand away to infinity. While this deterministic conclusion of instability is correct, we show that the Ellis wormhole reduces to Schwarzschild black hole only when the Ellis solution parameter γ assumes a complex value −i. We shall then reexamine stability of Ellis and phantom wormholes from the viewpoint of local and asymptotic observers by using a completely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Interestingly, the gravity fields of massless (M = 0) BNS and EBWH do not at all accrete matter since r ms is imaginary or infinitely large respectively, as is shown in Table 1, but both deflect light [see Eqs. (67) and (70)] since the Keplerian mass sensed by the photons is non-zero (m = 0, γ = 0). These cases are important since massless EBWH has actually been modeled as galactic halo objects in the Milky Way [79,80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the gravity fields of massless (M = 0) BNS and EBWH do not at all accrete matter since r ms is imaginary or infinitely large respectively, as is shown in Table 1, but both deflect light [see Eqs. (67) and (70)] since the Keplerian mass sensed by the photons is non-zero (m = 0, γ = 0). These cases are important since massless EBWH has actually been modeled as galactic halo objects in the Milky Way [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, under a restricted class of scalar field perturbations that vanish at the throat, EBWH has been shown to be stable [66]. Another recent new idea is that, due to curved spacetime, observation of instability or otherwise of EBWH could be perception-dependent depending on the location of the observer -while one observer perceives instability, another observer might perceive stability and conversely (see, for details, [67]). In any case, we do not contend the conclusion of instability but, instead of summarily ruling out EBWH, we advocate that verifiable diagnostics such as the accretion profiles (dealt with here), emission of gravitational waves, strong field lensing etc should be treated as observable verifications of EBWH, if there exists any in the universe [42,46].…”
Section: Introductionmentioning
confidence: 99%
“…However, some time ago, the question of (in)stability was analyzed from a completely different standpoint based not on challenging the mechanism of instability but on exploiting the fact that, in general relativity, observations are dependent on the location of the observer. It was then shown that while some observers observe instability of EBWH, there is a nonzero probability that some other observers could observe its stability from different locations [17]. Therefore, the present accretion scenario is relevant only to the latter types of observers.…”
Section: Introductionmentioning
confidence: 89%
“…It can also have applications in the studies of Primordial Black Holes (PBHs) where the accretion during the radiation dominated era is fast and takes place (e. g. [27,28]). Another potential application is related to the accretion of exotic cosmic fields that violate the weak energy condition, including phantom fields [29,30].…”
Section: Conclusion and Final Commentsmentioning
confidence: 99%